Efek Konsumsi Khamar dalam Perspektif Hadis - Irfan Alfiansyah; Muhamad Yoga Firdaus; Engkos Kosasih (Gunung Djati Conference Series, 2022)
The purpose of this study is to discuss the hadith about alcohol. This research method uses a qualitative type through literature study and content analysis. The results and discussion of this study include general views on khamr, hadith about khamr, and hadith prohibiting khamr. This study concludes that the hadith regarding khamr explains that khamr is something that can cover one's mind when consumed. Islam has looked down on khamr because it has many disadvantages compared to the benefits it brings. So that khamr is strictly prohibited to be consumed. This research is expected to provide benefits for all people about Islam, especially those related to the hadith regarding the prohibition of consuming khamr. This study has limitations in the preparation of the framework of thinking in the discussion of hadith about the prohibition of consumption of khamr so that a more comprehensive, integral and in-depth study is needed. This study recommends the importance of counseling to all Muslim audiences about the prohibition of consuming khamr.